Macroeconomic stability and transport companies’ sustainable development in the Eastern European Union - Comporek, Michał; Kowalska, Magdalena; Misztal, Anna (Journal of Business Economics and Management, 2022)
The paper’s primary aim is to evaluate the influence of macroeconomic stability on transport companies’ sustainable development in the eastern EU from 2008 to 2019. The first part discusses the theoretical problems. The empirical part includes the methodology, results of the research and conclusions. To determine the relationship between variables, we use Pearson’s R and the Ordinary Least Square Method. The contribution to knowledge is using the pentagon of macroeconomic stability to evaluate macroeconomic stabilisation’s influence on transport companies’ sustainable development. The results indicate that macroeconomic stability is one of the essential determinants of the transport companies’ sustainable development. According to Pearson’s R, the highest level of dependence is in Slovenia (0.96), Bulgaria (0.9), and Slovenia (0.83). The lowest is in Latvia (0.69). The OLS regression results indicate that the highest significance is in Slovakia (α1 = 1.994), the lowest is in Lithuania (α1 = 0.691). The states’ economic policies should favour the freedom to conduct business, create appropriate legal regulations, and support ecological investments. It is necessary to act for a stable and fair tax system, ensure access to finance. The issue is contemporary and requires further analysis. First published online 14 December 2021